Banks' supply of loans: When future monetary policy is uncertain - Kay Mitusch; Dieter Nautz (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
The most important policy instruments of the Bundesbank and of the coming European Central Bank involve lending to domestic credit institutions. In this monetary setup, banks use short-term central bank credits extensively in order to refinance long-term loans to the public, which makes them vulnerable to sudden monetary policy changes. We develop a loan supply model that captures distinguishing features of the European money supply process and show how money supply responds when future monetary policy is expected to become tighter or more uncertain. The results indicate that the controllability of borrowed reserves is of crucial importance for monetary policy practice.
urn:nbn:de:kobv:11-10056748
Keywords: E51; E52; 330; Loan and money supply; central bank lending; monetary policy instruments of the ECB; interest rate risk